Heat shock applied early in sporulation affects heat resistance of Bacillus megaterium spores - Sedlák, M; Vinter, V; Adamec, J; Vohradský, J; Voburka, Z; Chaloupka, J (Journal of bacteriology, 1993)
Cells of Bacillus megaterium 27 were challenged by a 30-min heat shock at 45 degrees C during various sporulation stages and then shifted back to a temperature permissive for sporulation (27 degrees C), at which they developed spores. Heat shock applied at 120 min after the end of the exponential phase induced synthesis of heat shock proteins (HSPs) in the sporangia and delayed the inactivation of spores at 85 degrees C. Several HSPs, mainly HSP 70, could be detected in the cytoplasm of these spores. An analogous HSP, the main HSP induced by increased temperature during growth, belongs to the GroEL group according to its N-terminal sequence. The identity of this protein was confirmed by Western blot (immunoblot) analysis with polyclonal antibodies against B. subtilis GroEL. Sporangia treated by heat shock immediately or 240 min after exponential phase also synthesized HSPs, but none of them could be detected in the spores in an appreciable amount. These spores showed only a slightly increased heat resistance.
Keywords: Time Factors; radioizotopy síry; vysoká teplota; Molecular Weight; proteiny teplotního šoku; elektroforéza v polyakrylamidovém gelu; Autoradiography; Bacterial Proteins; Kinetics; sírany; molekulová hmotnost; Sulfates; kinetika; Molecular Sequence Data; spory bakteriální; Cytoplasm; chaperon hsp60; molekulární sekvence - údaje; Sulfur Radioisotopes; časové faktory; Hot Temperature; Electrophoresis, Polyacrylamide Gel; sekvence aminokyselin; Chaperonin 60; cytoplazma; autoradiografie; bakteriální proteiny; Amino Acid Sequence; Heat-Shock Proteins; Bacillus megaterium; Spores, Bacterial